A study on university course and exam timetabling problems and methods: an optimization survey - Firdaus Khair, Ahmad; Makhtar, Mokhairi; Mazlan, Munirah; Afendee Mohamed, Mohamad; Nordin Abdul Rahman, Mohd (International Journal of Engineering and Technology, 2018)
The objective of this paper was to retrieve the overview approaches that have been proposed and classification constraints related to previ-ous papers of timetabling problems. Optimisation and scheduling are essential problems in every type of timetabling that can be considered as a non-deterministic polynomial. The objective of this paper to investigate the course and exam timetabling problem by presented classifi-cation table of set of constraints and describes the most reliable method that has been used to solve university timetabling problem. The re-sult of study concerned the two most successfully method that widely used for optimising course and exam timetable. The contribution of this study also help to provide knowledge and idea for further surveys.Â